First report of bacterial leaf spot disease on Pueraria montana var. thomsonii caused by Robbsia andropogonis in China - Cui, Xiaodong; Cai, Yongpeng; Chen, Runzhen; Liu, Qiongguang (Plant disease, 2022)
Pueraria montana var. thomsonii (Hereinafter referred to as Pmt) belongs to the Leguminosae and is widely distributed in China, Laos, Thailand, Myanmar, Bhutan and other Asian countries. The plant is called "Fenge" in China, and its root is widely used in medicine and food. In recent years, an unknown leaf spot disease of Pmt has occurred in Gaoming, Zhaoqing and Yunfu districts of Guangdong Province in China, where 1,600 hectares of Pmt plants were affected. The incidence rate of plants were more than 80% and led to 10-15% death of Pmt plants in Gaoming district. . In the early stage of the disease, radiating and water-soaking lesions appeared between the main veins and side veins of Pmt leaves. After the spread of the lesions, they formed brown and short strips with yellow haloes around them, which led to leaf shedding, plant death and decline of production. To isolate bacteria, diseased leaves were surface sterilized with 0.6% sodium hypochlorite solution for 30 s, followed by three consecutive rinses in distilled water. The leaves were aseptically macerated, and the macerate streaked on PDA medium. Whitish to dull white, mucoid, raised, round, and translucent colonies were obtained. All isolates were gram-negative and had a single, polar, sheathed flagellum. Sequences (approx. 1,458 bp each) of the 16S rRNA gene amplified from five isolates (FG2, FG3, FG9, FG12 and FG17) using primer pair 27F/1492R (Lane et al,1991) (GenBank Accession Nos. OL677034, OL677351, OL677352, OL677353 and OL677354 respectively) shared 99.93% sequence identity with that of Robbsia andropogonis (Synonyms: Burkholderia andropogonis) (Lopes-Santos et al,2017) type strain LMG2129 (NR104960.1). The specific 410-bp and 704-bp target fragments were also amplified from isolates using R. andropogonis-specific primers Pf/Pr (Bagsic et al,1995) and LJ23f/LJ24R (Duan et al,2009). The four housekeeping genes atpD, lepA, gyrB and rpoD were partially sequenced for FG9 isolates using primers atpD-F3/atpD-R3, lepA-F2/lepA-R, LJ23f/LJ24R and LJ25f/LJ26r (Duan et al,2009; Estrada-De et al,2013) respectively. Multilocus sequence analyses confirmed the isolates from Pmt as R. andropogonis. Physiological and biochemical tests revealed the isolates are negative for oxidase, arginine dihydrolase, saccharose and betaine, and positive for sorbitol, lactose and galactose (Gillis et al,1995; Lopes-Santos et al,2017). In addition, all isolates caused a hypersensitive reaction on leaves of Nicotiana benthamiana and were pathogenic to some crops, including maize (Zea mays), sorghum (Sorghum bicolor), carnation (Dianthus caryophilus), common bean (Phaseolus vulgaris), tomato. Five isolates (FG2, FG3, FG9, FG12 and FG17) pathogenicity were tested twice with a total of three replications per isolate. Two young leaves each of 3-month-old Pmt plants grow in greenhouse were sprayed a bacterial suspension at 108 CFU/ml, then covered the inoculated leaves individually with plastic bags for 24 h, and incubated at 100% relative humidity with 16 h of daylight at 30°C and 8 h of darkness at 22°C in a greenhouse. Radiating and water-soaked lesions with yellow haloes were observed between the main veins and side veins of Pmt leaves 5 days after inoculation and were similar to those caused by R. andropogonis in the field. Koch's postulates were fulfilled by reisolating bacteria from typical lesions on inoculated plants. And the reisolated bacteria were identical to the inoculated ones. To our knowledge, this is the first report of R. andropogonis on Pueraria montana var. thomsonii in China.